Social Critique in the Monologue 'Balada Sumarah' by Tentrem Lestari - Harianja, Anjelina Septiana; Harahap, Nurhayati; Triana, Ade (Peneliti.net, 2023)
This research explores social criticism within Tentrem Lestari's monologue drama,